2003
DOI: 10.1055/s-2003-38880
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effects of a Mixture of Fatty Acids Isolated and Purified from Sugar Cane Wax Oil

Abstract: The anti-inflammatory and analgesic effects of FAM, a defined mixture of fatty acids isolated from sugar cane (Saccharum officinarum L.), was evaluated. Oral administration of this mixture showed anti-inflammatory activity in the cotton pellet granuloma assay and in the carrageenin-induced pleurisy test, both in rats, as well as in the peritoneal capillary permeability test in mice. In addition, FAM showed analgesic properties in the hot-plate model and in the acetic acid-induced writhings test, both in mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 5 publications
1
19
0
1
Order By: Relevance
“…Also, in this study, the SPB group showed a 2% higher body weight gain than the control. Alternatively, SCE has displayed a wide range of biological effects including immunostimulation (El-Abasy et al, 2002), antiinflammatory activity (Ledon et al, 2003), activity as a vaccine adjuvant (El-Abasy et al, 2003) and anti-stress effects (Brekhman et al, 1978). Studies on chickens indicate that SCE acts as an adjuvant and has a protective effect against Eimeria tenella infection (El- Abasy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in this study, the SPB group showed a 2% higher body weight gain than the control. Alternatively, SCE has displayed a wide range of biological effects including immunostimulation (El-Abasy et al, 2002), antiinflammatory activity (Ledon et al, 2003), activity as a vaccine adjuvant (El-Abasy et al, 2003) and anti-stress effects (Brekhman et al, 1978). Studies on chickens indicate that SCE acts as an adjuvant and has a protective effect against Eimeria tenella infection (El- Abasy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Those products have been widely used as supplements in animal foods to boost innate immunity against infections [9,15,24]. Byproducts of sugar production from sugar cane have been reported to have a wide range of biological activities [12,14,17,22], especially antioxidative activities, phylactic activities, and other physiological functions [1,18,19,21]. Protective phylactic effects against viral and bacterial infections could be exploited to reduce the use of antibiotics in the pig industry.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar cane extract (SCE) is a natural product which has displayed a wide range of biological effects including immunostimulation [8], anti-thrombosis activity [17], antiinflammatory activity [14], vaccine adjuvant [7], anti-oxidant activity [18,21], modulation of acetylcholine release [2], and anti-stress effects [3]. Study on mice inoculated with a minimum lethal dose of pseudorabies virus following with 3 consecutive days of oral administration with SCE showed a significant decrease in mortality (Koge, unpublished).…”
mentioning
confidence: 99%
“…Pseudorabies virus (PrV) has been recognized as one of the most important primary pathogens for PRDC in fattening pigs [5,13,28] and antibiotics are commonly used to prevent secondary bacterial infections. As the abuse of antibiotics in veterinary medicine has been of particular concern from the viewpoint of public health, besides vaccination, major strategies against PRDC are to improve the managerial systems and environmental conditions and to modulate host immunocompetence.Sugar cane extract (SCE) is a natural product, which has displayed a wide range of biological effects including immunostimulation [11], anti-inflammatory activity [19], activity as a vaccine adjuvant [10], and anti-stress effects [4]. Studies on chickens indicate that SCE acts as an adjuvant and has a protective effect against Eimeria tenella infection [9].…”
mentioning
confidence: 99%
“…Sugar cane extract (SCE) is a natural product, which has displayed a wide range of biological effects including immunostimulation [11], anti-inflammatory activity [19], activity as a vaccine adjuvant [10], and anti-stress effects [4]. Studies on chickens indicate that SCE acts as an adjuvant and has a protective effect against Eimeria tenella infection [9].…”
mentioning
confidence: 99%